Synthesis of Supercapacitor from Cocoa Fruit Peel Activated Carbon for Energy Storage - Rahma Fikri Nuradi; Mulda Muldarisnur; Yuli Yetri (Universitas Andalas, 2022)
The supercapacitor electrode has been synthesized using activated carbon from cocoa pods. Activated carbon was prepared by first drying the raw materials under the sunlight and followed by oven drying, pre-carbonization, milling, sieving, and chemical activation with 0.3 M and 0.4 M KOH solution. After chemical activation, the activated carbon was printed into pellet form, carbonized at a temperature of 600 °C, followed by physical activation at a temperature of 700 °C for four hours before polishing. We found that the optimum conditions are 700 °C and 0.4 M. The density of the obtained carbon electrode is 0.810 g/cm3. The SEM micrographs show the formation of pores with a diameter of 0.44 μm and 0.98 μm. The carbon content in the electrode sample measured using electron dispersive spectroscopy is 91.49%. The XRD data shows that the carbon electrode is amorphous with a diffraction angle (2θ) at 23.569° and 44.781°. The optimum specific capacitance of the supercapacitor is 140.2 F/g obtained for the sample activated for 2.5 hours.